2006
DOI: 10.3758/bf03213919
|View full text |Cite
|
Sign up to set email alerts
|

Is retrieval success a necessary condition for retrieval-induced forgetting?

Abstract: When information is retrieved from memory, it becomes more recallable than it would have been otherwise. Other information associated with the same cue or configuration of cues, however, becomes less recallable. Such retrieval-induced forgetting (Anderson, Bjork, & Bjork, 1994) appears to reflect the suppression of competing nontarget information, with this suppression facilitating the selection of target information. But is success at such selection a necessary condition for retrieval-induced forgetting? Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
158
2
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(183 citation statements)
references
References 16 publications
21
158
2
2
Order By: Relevance
“…For instance, in research on retrieval-induced forgetting, some authors have reported full recovery from inhibition after a day or more (Chan, 2009 ;MacLeod & Macrae, 2001 ;Saunders & MacLeod, 2002 ) , concluding that the effect is transient, whereas other authors have reported inhibition after 24 h (Ford, Keating, & Patel, 2004 ;Conroy & Salmon, 2005 ;Conroy & Salmon, 2006 ;Garcia-Bajos, Migueles, & Anderson, 2009 ;Storm et al, 2006 ;Racsmány, Conway, & Demeter, 2010 ;Tandoh & Naka, 2007 ) . Indeed, Garcia-Bajos, Migueles, and Anderson found, using an eyewitness memory video, retrieval-induced forgetting after a week that was signifi cant and undiminished (Garcia-Bajos et al, 2009 ) .…”
Section: Effects Of Retention Interval On the Effect Are Unclearmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in research on retrieval-induced forgetting, some authors have reported full recovery from inhibition after a day or more (Chan, 2009 ;MacLeod & Macrae, 2001 ;Saunders & MacLeod, 2002 ) , concluding that the effect is transient, whereas other authors have reported inhibition after 24 h (Ford, Keating, & Patel, 2004 ;Conroy & Salmon, 2005 ;Conroy & Salmon, 2006 ;Garcia-Bajos, Migueles, & Anderson, 2009 ;Storm et al, 2006 ;Racsmány, Conway, & Demeter, 2010 ;Tandoh & Naka, 2007 ) . Indeed, Garcia-Bajos, Migueles, and Anderson found, using an eyewitness memory video, retrieval-induced forgetting after a week that was signifi cant and undiminished (Garcia-Bajos et al, 2009 ) .…”
Section: Effects Of Retention Interval On the Effect Are Unclearmentioning
confidence: 99%
“…Finally, even if thought substitution induces a negative control effect, this by no means implies that the effect is driven by associative interference, but rather could refl ect inhibitory processes associated with retrieval-induced forgetting. Indeed, prior work on retrieval-induced forgetting has established that the mere effort to retrieve a target, even if not successful, can induce inhibition of competing items, suggesting that one should not presume that thought substitution effects are driven by interference (Storm, Bjork, Bjork, & Nestojko, 2006 ;see Storm, 2010 for a review). Evaluation of these possibilities would require the examination of strategies other than thought substitution.…”
Section: Thought Substitutes Increase the Effectmentioning
confidence: 99%
“…Previous work by Bäuml (2002) has suggested that semantic generation can lead to retrieval-induced forgetting; that is, semantically generating new exemplars of a category can impair memory for other, previously studied members (see also Storm, Bjork, Bjork, & Nestojko, 2006 (Roediger & Schmidt, 1980). If output interference influences recall, then retrieval-induced forgetting may be evident only for participants who retrieve Rp items early during free recall.…”
Section: Experiments 1 Does Mental Imagery Evoke Retrieval-induced Formentioning
confidence: 99%
“…For example, there is evidence that retrieval-induced forgetting is competition dependent-that the extent to which items suffer retrieval-induced forgetting is determined by the extent to which they compete during retrieval practice (e.g., Anderson et al, 1994;Storm, Bjork, & Bjork, 2007; for a review, see Storm, 2011b). There is also evidence that retrieval-induced forgetting is strength independent-that the extent to which practiced items are strengthened does not determine whether unpracticed items are forgotten (e.g., Anderson, Bjork, & Bjork, 2000;Bäuml, 2002;Storm et al, 2006). Research examining individual differences has also supported the inhibitory account.…”
Section: Discussionmentioning
confidence: 79%
“…For example, just as retrieval success is not a necessary condition for retrieval-induced forgetting (Storm, Bjork, Bjork, & Nestojko, 2006;Storm & Nestojko, 2010), problem-solving success is not a necessary condition for problem-solving-induced forgetting (Storm et al, 2011). Attempting to solve problems caused participants to forget fixating associates even when those attempts failed.…”
Section: Introductionmentioning
confidence: 99%